Five Years Lost: Youth Inclusion in the Rohingya Response. (March 2023) - Islam, Imrul; Naing, Zia
While youth are routinely lauded as "change-makers, " they are often underserved and unsupported in refugee responses. As the Rohingya face protracted displacement in Bangladesh, what is the state of youth inclusion in the response? Do youth and adolescents feel supported, or are they ignored and left behind? To answer these questions, the paper uses: Literature on youth participation and inclusion in humanitarian programming; Key informant interviews with practitioners from national and international non-governmental organizations (NGOs) and UN agencies; Focus group discussions and key informant interviews with refugee individuals and groups across nine camps for Rohingya refugees in Bangladesh. It finds that: Refugee Rohingya youth and adolescents remain firmly on the margins of humanitarian programming, and are largely excluded from decision-making processes; Approximately 96 percent of surveyed youth between 18 and 24 years of age report being unemployed; For surveyed women aged 18–24 years, unemployment rates bordered on 99 percent; and Stress and anxiety are omnipresent amongst the community: an overwhelming majority of respondents reported experiencing disturbing thoughts and resorting to negative coping mechanisms. The paper ends with a series of recommendations to the Strategic Executive Group (SEG) and the Inter-Sector Coordination Group (ISCG), to donors, the international community, and the government of Bangladesh. 1